Body Mass, Nutrition, and Disease: Current Net Nutrition during US Economic Development - Scott A. Carson (Center for Economic Studies and Ifo Institute (CESifo), 2020)
When other measures for material welfare are scarce or unreliable, the use of average stature and body mass index (BMI) values is common. BMI reflects the current difference between calories consumed, calories required for work, and to withstand the physical environment. This study evaluates 19th century macro-level nutrition and diseases associated with US BMI variation. Body mass was positively related to calories from dairy products and inversely related to malaria, which had a larger effect on net-nutrition than cholera. After controlling for nutrition and disease, black BMIs and weights were greater than whites, indicating that 19th century social preferences are an unlikely explanation for taller, fairer complexioned whites.
Keywords: I12; I31; J31; J70; N31; 330; nineteenth century US health; BMI variation by characteristics; malnourishment